Meristics of the Etruscan goby Padogobius nigricans - Scalici, Massimiliano; Gibertini, Giancarlo (HIDROBIOLÓGICA, 2017)
The Etruscan goby Padogobius nigricans is a running water dwelling vulnerable species inhabiting the Tuscano-Latium district. Since many aspects of the biology of this species are still unknown, our research was aimed at describing its meristic features to observe how ontogeny and sexual dimorphism affect the studied traits, and thus provide useful characters for preservation purposes. Significant intra- and inter-population differences were detected for some meristic traits. In particular most of the studied parameters were affected by ontogeny but not sexual dimorphism except for the caudal fin, for which different values were registered for both sexes in two of the three studied populations. This suggests that the meristic pattern may change from one population to another. Considering the short geographic distance and the similar environmental conditions among the analysed locations, this differentiation was not expected. From the results of this research, there seems to be a considerable scope for further studies on P. nigricans due to the paucity of data regarding the morphology and meristics of this species.